2015
DOI: 10.1091/mbc.e14-12-1632
|View full text |Cite
|
Sign up to set email alerts
|

Expression, sorting, and segregation of Golgi proteins during germ cell differentiation in the testis

Abstract: A total of 1318 proteins characterized in the male germ cell Golgi apparatus reveal a new germ cell–specific Golgi marker and a new pan-Golgi marker for all cells. The localization of these and other Golgi proteins reveals differential expression linked to mitosis, meiosis, acrosome formation, and postacrosome Golgi migration and destination in the late spermatid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 91 publications
3
50
0
Order By: Relevance
“…Acrosome development occurs during early spermiogenesis and results from the assembly of pro-acrosomic vesicles. These vesicles originate from the Golgi apparatus and GRASP55 has been reported to be specifically associated to the Golgi apparatus and acrosome of step 1–7 rat spermatids, which suggests that this protein plays a specific function in acrosome development [45]. Our results confirmed this hypothesis and demonstrated that this function relies, at least partially, on the transient interaction between GRASP55 and JAM-C during early spermiogenesis in mice (step 1–7 spermatids).…”
Section: Discussionsupporting
confidence: 84%
“…Acrosome development occurs during early spermiogenesis and results from the assembly of pro-acrosomic vesicles. These vesicles originate from the Golgi apparatus and GRASP55 has been reported to be specifically associated to the Golgi apparatus and acrosome of step 1–7 rat spermatids, which suggests that this protein plays a specific function in acrosome development [45]. Our results confirmed this hypothesis and demonstrated that this function relies, at least partially, on the transient interaction between GRASP55 and JAM-C during early spermiogenesis in mice (step 1–7 spermatids).…”
Section: Discussionsupporting
confidence: 84%
“…In this way, we could compare if the protein composition of the Golgi cisternae of the HB was comparable to that of germ cells of the testis. Protein abundances were estimated from spectral counting (redundant peptides) with a comparison of the proteins characterized in each of the n = 3 separate isolates of both the testis Golgi fractions with those of HB isolated from epididymal spermatozoa (Au et al ., ,b). Proteins were subdivided into 22 functional categories as described by Gilchrist et al .…”
Section: Isolation and Characterization Of The Protein Makeup Of The mentioning
confidence: 99%
“…In order to determine a functional role for the HB of spermatozoa, subcellular fractions of isolated HBs from adult rat caput epididymal spermatozoa were characterized by quantitative tandem mass spectrometry (Au et al ., 2015a). Concomitantly, the spherical compact Golgi apparatus characteristic of germ cells was isolated from whole testis homogenates (Au et al ., 2015b). In this way, we could compare if the protein composition of the Golgi cisternae of the HB was comparable to that of germ cells of the testis.…”
Section: Isolation and Characterization Of The Protein Makeup Of The mentioning
confidence: 99%
See 1 more Smart Citation
“…There are close to 500 glycogenes encoded in the human genome , whose expression is regulated at multiple levels: transcription, regulation of transcript and/or protein half‐life. Several studies have demonstrated a change in expression of glycogenes in response to cell intrinsic or extrinsic factors . For instance, epigenetic mechanisms have been shown to regulate the changes in glycogene expression that leads to a switch from neutral globo and lacto series GSLs to acidic ganglio‐series GSLs during neuronal differentiation .…”
Section: Factors Affecting Glycan Outputmentioning
confidence: 99%